"Donating our bodies to science": A discussion about autopsy and organ donation in Turner syndrome. Issue 1 (11th January 2019) - Prakash, Siddharth K.; San Roman, Adrianna K.; Crenshaw, Melissa; Flink, Barbara; Earle, Kimberly; Los, Evan; Bonnard, Åsa; Lin, Angela E.
Abstract : At the Third Turner Resource Network Symposium, a working group presented the results of collaborative discussions about the importance of autopsy in Turner syndrome (TS). Considerable gaps in understanding the causes of death in TS can only be closed by more frequent death investigations and autopsies. The presentation included an overview of autopsy methods, strategies for utilizing autopsy, and biobanking to address research questions about TS, and the role of palliative care in the context of autopsy. This review highlights strategies to promote autopsy and tissue donation, culminating with an action plan to increase autopsy rates in the TS community.